Expansion of Authority of The Ombudsman Indonesia in Giving Sanctions Against Maladministration of Public Services - Maulina, Dewi; Hidayat, Arif (Universitas Negeri Semarang, 2025)
Public services should ideally be organized to ensure equal access for all citizens. However, in practice, maladministration is often found that is detrimental to the rights of the community. The Ombudsman of the Republic of Indonesia as a state institution authorized to supervise the implementation of public services, has the authority to issue recommendations as a form of correction for maladministration by state administrators. However, the implementation of these recommendations is often ignored, which reflects the weak law enforcement mechanism for the results of this supervision. This study aims to examine: (1) the existence of the authority of the Ombudsman of the Republic of Indonesia in supervising the implementation of public services based on the provisions of laws and regulations; and (2) the legal design of the expansion of the Ombudsman's authority in imposing sanctions for maladministration based on the perspective of dynamic governance. The research method used is normative legal. The results of the study indicate that the Ombudsman's authority is based on strong historical and legal constructions, and has implications for institutions and the protection of community rights. The design of the expansion of authority is assessed through three indicators of dynamic governance, namely: adaptability to change, policy innovation, and handling policy complexity. This study recommends strengthening the legal and institutional basis to ensure that the Ombudsman's recommendations have effective binding power in the national legal system.